Beyond CPAP: modifying upper airway output for the treatment of OSA - Gruenberg, Eli; Cooper, Jessica; Zamora, Tania; Stepnowsky, Carl; Vahabzadeh-Hagh, Andrew M.; Malhotra, Atul; Nokes, Brandon (Frontiers in Neurology, 2023)
Obstructive Sleep Apnea (OSA) is exceedingly common but often under-treated. Continuous positive airway pressure (CPAP) has long been considered the gold standard of OSA therapy. Limitations to CPAP therapy include adherence and availability. The 2021 global CPAP shortage highlighted the need to tailor patient treatments beyond CPAP alone. Common CPAP alternative approaches include positional therapy, mandibular advancement devices, and upper airway surgery. Upper airway training consists of a variety of therapies, including exercise regimens, external neuromuscular electrical stimulation, and woodwind instruments. More invasive approaches include hypoglossal nerve stimulation devices. This review will focus on the approaches for modifying upper airway muscle behavior as a therapeutic modality in OSA.